2020
DOI: 10.1007/s12356-020-00064-6
|View full text |Cite
|
Sign up to set email alerts
|

Design space for bifurcation buckling of laser-welded web-core sandwich plates as predicted by classical and micropolar plate theories

Abstract: The strength of laser-welded web-core sandwich plates is often limited by buckling. In design of complex thin-walled structures the combination of possible structural and material combinations is basically infinite. The feasibility of these combinations can be assessed by using analytical, numerical and experimental methods. At the early design stages such as concept design stage, the role of analytical methods is significant due to their capability for parametric description and extremely low computational ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…For example, size-effects within lowdimensional (micro-and nano-scale) structures, such as carbon nanotubes, emerge due to the long-range forces that become more prevalent at these scales [5,6]. Several studies have also demonstrated the presence of nonlocal interactions at the macro-scale in complex structures like porous solids [7][8][9], periodic structures [10,11], intentionally engineered nonlocal structures [12], and sandwiched structures [13]. The inability of the classical (local) continuum theory to capture the nonlocal effects has been one of the main drivers fostering the development of nonlocal continuum theories.…”
Section: Introductionmentioning
confidence: 99%
“…For example, size-effects within lowdimensional (micro-and nano-scale) structures, such as carbon nanotubes, emerge due to the long-range forces that become more prevalent at these scales [5,6]. Several studies have also demonstrated the presence of nonlocal interactions at the macro-scale in complex structures like porous solids [7][8][9], periodic structures [10,11], intentionally engineered nonlocal structures [12], and sandwiched structures [13]. The inability of the classical (local) continuum theory to capture the nonlocal effects has been one of the main drivers fostering the development of nonlocal continuum theories.…”
Section: Introductionmentioning
confidence: 99%
“…For stiffened panel only, such modes can be calculated using e.g., Brubak et al [26] presented semi-analytical approach. Similar local effects also occur in buckling modes, and for web-core sandwich panels they were captured using correction for ESL-FSDT in [27] or more advanced micropolar ESL-FSDT plate model [28], [29], which is based on non-classical continuum mechanics where microrotations and -inertia are included. In [30], natural frequencies of stiffened panel were obtained by combining ESL-model frequencies with the local plate between stiffener frequencies, using the assumption that stiffeners with plate between them act as springs and masses in series.…”
Section: Introductionmentioning
confidence: 99%